Synthesis of shared aperture thinned interleaved arrays with elements in concentric rings - Zhigang GU; Longjun LI; Jikuan HU (Dianxin kexue)
Among planar array antennas, concentric ring array (CRA) antennas have received considerable interest since it is symmetric and provides invariant beam pattern for 360° azimuthal coverage.In case of limited antenna aperture, there is great value to thinned interleaved CRA with low peak side lobe levels and a narrow main beam.The application of the cubic interpolation and density-weighting method in shared aperture array design was demonstrated by the low peak side lobe level synthesis of CRA.By adopting the Fourier-Bessel transform the relationship between the element’s excitation and array pattern, thinned interleaved problems were formulated as time-frequency synthesis problems.On the basis of the density-weighting method, element excitations of interleaved sub-array were carefully selected in an odd-even manner, which ensured the pattern matching of the generated sub-array.The iterative FFT algo rithm was adopted to thin the concentric ring array.Simulation results show that the proposed algorithm can achieve a favorable thinned and interleaved concentric ring array design with matched power patterns and low peak sidelobe levels.The problem of thinned and interleaved concentric ring arrays is solved, and the design of multi-function shared aperture thinned interleaved arrays with elements in concentric rings is realized.